(3QSGFd GdTgjO GdKGfjs - (3GdYGedj GdLYHj, GdTgjO GdKGfj, Rjf GdOjf Hf Ydj Hf CMeO, (B966 (3gs ((3Rjf GdOjf Hf Ydj Hf MeO ,ZOGbI , UGdM Hf MSjf YHO GdYGdjs)
(3ChdgG (B:s
(3HYO MeO Gddg (B... (3agPg LedI ef GdcdGe aj JMbjb eSCdI abgjI TgjQI aj GdaJhQ (B.. (3Cf GdCUMGH QVhGf Gddg Ydjge McehG HCf GdeSGaQ EPG fhi GbGeI YTQI CjGe aj ZjQ HdOg EeG Ydi QCS GdeSGaI Ch aj CKfGFgG GfJbd (B...s
(3BNQgG (B:s
.. (3Ydi cdGe GHf EOQjS aj GdhVhA GdeJbOe Ydi GdZSd Cfg jfhj Hg GdGSJHGMI dYOe GQJaGY GdMOK YOe GdLhGR ajgG CjVG dcf dG bGFd Hg gfG dCf GHf GOQjS dG jhLH GdhVhA efgG hGddg CYde hUdi Gddg Ydi eMeO hBdgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3\ 64s
(3GdPQjYI (B10\808s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis